2014
DOI: 10.1002/smll.201400911
|View full text |Cite
|
Sign up to set email alerts
|

High‐Durable AgNi Nanomesh Film for a Transparent Conducting Electrode

Abstract: Uniform metal nanomesh structures are promising candidates that may replace of indium-tin oxide (ITO) in transparent conducting electrodes (TCEs). However, the durability of the uniform metal mesh has not yet been studied. For this reason, a comparative analysis of the durability of TCEs based on pure Ag and AgNi nanomesh, which are fabricated by using simple transfer printing, is performed. The AgNi nanomesh shows high long-term stability to oxidation, heat, and chemicals compared with that of pure Ag nanomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
102
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(108 citation statements)
references
References 48 publications
4
102
1
1
Order By: Relevance
“…22 Meanwhile, previous studies have shown that AgNW networks on flexible substrates have superior flexibility compared to ITO/flexible substrate. 10,23 As expected, as shown in Fig. S2 and S3 in supplementary material, the ITO/PET shows less mechanical flexibility than the AgNW network/PET at bending radii of 10 mm or less.…”
Section: Resultssupporting
confidence: 62%
See 2 more Smart Citations
“…22 Meanwhile, previous studies have shown that AgNW networks on flexible substrates have superior flexibility compared to ITO/flexible substrate. 10,23 As expected, as shown in Fig. S2 and S3 in supplementary material, the ITO/PET shows less mechanical flexibility than the AgNW network/PET at bending radii of 10 mm or less.…”
Section: Resultssupporting
confidence: 62%
“…In general, the minimum FoM value necessary for transparent electronic applications is 35. 10,22,23 Therefore, we expect that the transfer-printed Ni micromesh could be used as a transparent electronic electrode, heater, or sensor in various optoelectronic devices. These results also indicate that the optical transmittance, sheet resistance, and FoM value of the metal mesh can be controlled by changing the mesh thickness.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to evaluate the opto-electrical property of AgNF TCE and compare it with other latest metal network TCEs, we used a figure of merit (FoM). The FoM for the nanostructure TCE can be calculated by the following equation [7,[12][13][14].…”
Section: Electrical and Optical Properties Of Agnf Transparent Conducmentioning
confidence: 99%
“…[1][2][3][4] With regard to efficiency,P SCs may be suitable for av ariety of applications because of their low cost, simple fabrication process, light weight, and high mechanical flexibility.U nfortunately,t he high efficiency of PSCs has mostly originated from highly rigid conductive glass substrates based on indium tin oxide (ITO) with poor mechanical flexibility.F or this reason, various alternative transparent conductive electrode (TCE) candidates have been researched, such as graphene, [5][6][7][8] carbon nanotubes, [9][10][11][12] metal nanowires, [13][14][15][16][17] poly (3,4-ethylenedioxythiophene): poly(styrenesulfonate) (PE-DOT:PSS), [18][19][20][21][22][23] and metal mesh grids, [24][25][26][27] to replacet he conventional TCEs for flexible PSCs.A mong these TCE alternatives, the Ag mesh electrode is an attractive candidate because of its variousa dvantages,s uch as its good electrical, optical, and flexible characteristics, the possibility of mass production, and large area processibilityf or flexible optoelectronic devices. [28][29][30] Nonetheless, the direct applicationo ft he Ag mesh TCE for organic electronics still has drawbacks such as:1 )the possibility of shorting in the device because of the high pitch of the metal grid with as cale of several micrometers, 2) current inhomogeneity in the device based on the mesh structure, and 3) adhesionp roblems between the Ag mesh electrode and the flexible substrate. To solve the aforementioned problems, some researchers have suggestedt he use of metal mesh electrodesf abricated by nanoimprinting technologyb yu sing at hermalo re -beam evaporator.…”
Section: Introductionmentioning
confidence: 99%